Ultrastaging methods of sentinel lymph nodes in endometrial cancer ‐ a systematic review. Issue 5 (May 2021) - Burg, Lara C; Hengeveld, Ellen M; in 't Hout, Joanna; Bulten, Johan; Bult, Peter; Zusterzeel, Petra L M
Abstract : Objective : Sentinel lymph node mapping has emerged as an alternative to lymphadenectomy in evaluating the lymph node status in endometrial cancer. Several pathological methods to examine the sentinel lymph node are applied internationally. The aim of this study was to determine the value of ultrastaging and to assess the ultrastaging method with the highest detection rate of metastases. Methods : A systematic review was conducted. Inclusion criteria were: pathologically‐confirmed endometrial cancer with sentinel lymph node mapping, report of the histological outcomes, metastases found by hematoxylin and eosin staining and metastases found by ultrastaging were separately mentioned, and description of the ultrastaging method. The primary outcome was the detection of metastases found by ultrastaging that were not detected by routine hematoxylin and eosin staining. The secondary outcome was the difference in detection rate of metastases between several ultrastaging methods. Random effects meta‐analyses were conducted. Results : Fifteen studies were selected, including 2259 patients. Sentinel lymph nodes were examined by routine hematoxylin and eosin staining. Subsequently, multiple ultrastaging methods were used, with differences in macroscopic slicing (bread‐loaf/longitudinal), number of microscopic slides, and distance between slides, but all used immunohistochemistry. A positive sentinel lymph node was found in 14% of patients. In 37% of these, this was detected only by ultrastaging. Using more ultrastaging slides did not result in a higher detection rate. Bread‐loaf slicing led to a higher detection rate compared with longitudinal slicing (mean detection rates 53% and 33%, respectively). Conclusion : Pathological ultrastaging after routine hematoxylin and eosin staining in endometrial cancer patients has led to an increased detection rate of sentinel lymph node metastases. Different ultrastaging methods are used, with a preference for bread‐loaf slicing. However, due to the large heterogeneity of the studies, assessing which ultrastaging method has the highest detection rate of sentinel lymph node metastases was not possible.